Histone H3K9 Trimethylase Eggless Controls Germline Stem Cell Maintenance and Differentiation - Wang, Xiaoxi (Public Library of Science, 2011)
Epigenetic regulation plays critical roles in the regulation of cell proliferation, fate determination, and survival. It has been shown to control self-renewal and lineage differentiation of embryonic stem cells. However, epigenetic regulation of adult stem cell function remains poorly defined. Drosophila ovarian germline stem cells (GSCs) are a productive adult stem cell system for revealing regulatory mechanisms controlling self-renewal and differentiation. In this study, we show that Eggless (Egg), a H3K9 methyltransferase in Drosophila, is required in GSCs for controlling self-renewal and in escort cells for regulating germ cell differentiation. egg mutant ovaries primarily exhibit germ cell differentiation defects in young females and gradually lose GSCs with time, indicating that Egg regulates both germ cell maintenance and differentiation. Marked mutant egg GSCs lack expression of trimethylated H3K9 (H3k9me3) and are rapidly lost from the niche, but their mutant progeny can still differentiate into 16-cell cysts, indicating that Egg is required intrinsically to control GSC self-renewal but not differentiation. Interestingly, BMP-mediated transcriptional repression of differentiation factor bam in marked egg mutant GSCs remains normal, indicating that Egg is dispensable for BMP signaling in GSCs. Normally, Bam and Bgcn interact with each other to promote GSC differentiation. Interestingly, marked double mutant egg bgcn GSCs are still lost, but their progeny are able to differentiate into 16-cell cysts though bgcn mutant GSCs normally do not differentiate, indicating that Egg intrinsically controls GSC self-renewal through repressing a Bam/Bgcn-independent pathway. Surprisingly, RNAi-mediated egg knockdown in escort cells leads to their gradual loss and a germ cell differentiation defect. The germ cell differentiation defect is at least in part attributed to an increase in BMP signaling in the germ cell differentiation niche. Therefore, this study has revealed the essential roles of histone H3K9 trimethylation in controlling stem cell maintenance and differentiation through distinct mechanisms.